Szmalec i „żydowskie złoto” - Molisak, Alina (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The article recalls two literary texts which signalled the facts denied or marginalized in Polish historical memory: a phenomenon of szmalcownictwo (blackmailing for money of Jews who were hiding) and the search for “Jewish gold”. The context for the study of both narrations is the contemporary historical discourse and its evolution that can be observed in the recent 10-20 years in the Polish public sphere.